2017
DOI: 10.1111/jocn.13666
|View full text |Cite
|
Sign up to set email alerts
|

Changes in self‐efficacy, collective efficacy and patient outcome following interprofessional simulation training on postpartum haemorrhage

Abstract: Aims and objectives. To examine whether interprofessional simulation training on management of postpartum haemorrhage enhances self-efficacy and collective efficacy and reduces the blood transfusion rate after birth. Background. Postpartum haemorrhage is a leading cause of maternal morbidity and mortality worldwide, although it is preventable in most cases. Interprofessional simulation training might help improve the competence of health professionals dealing with postpartum haemorrhage, and more information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 41 publications
4
57
0
4
Order By: Relevance
“…The prevalence of blood transfusions at KCMC from 3.2 to 1.7% pre-post training corresponds with findings from a retrospective study on similar simulation training in Norway, where the prevalence of blood transfusions dropped from 3.4 to 2% after training [ 11 ]. Another Norwegian study on simulation training showed a transfusion rate pre-post training of 4.6 and 4.6% respectively [ 44 ]. The reported overall maternal transfusion rate at KCMC was according to Macheku et al 5.7% during a period of 10 years, including antenatal hemorrhage counting for 74%, PPH for 26% of the incidents [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of blood transfusions at KCMC from 3.2 to 1.7% pre-post training corresponds with findings from a retrospective study on similar simulation training in Norway, where the prevalence of blood transfusions dropped from 3.4 to 2% after training [ 11 ]. Another Norwegian study on simulation training showed a transfusion rate pre-post training of 4.6 and 4.6% respectively [ 44 ]. The reported overall maternal transfusion rate at KCMC was according to Macheku et al 5.7% during a period of 10 years, including antenatal hemorrhage counting for 74%, PPH for 26% of the incidents [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The encounters were recorded for asynchronous moderation with a different examiner. Last, examinations involving all three stakeholders (candidate, patient, examiner) were modified to minimise patient participation These were achieved using task-trainers or simulations with mannequins and hybrid simulations (Egenberg et al 2017) or simulated patients. Where patient participation was crucial, candidates were instructed to follow prevailing infection control guidelines with the use of PPE during the assessment.…”
Section: Assessments and Response To Pandemicsmentioning
confidence: 99%
“…In a correlational study, Lee and Ko (2010) found that collective efficacy had a small but significant association with reduced error in nursing performance among a sample of Korean hospital nurses. One collective efficacy interventions among hospital staff was associated with better patient outcomes (Egenberg et al, 2016). Among nursing students, an interprofessional education intervention was associated with greater perceptions of collective efficacy (Wong et al, 2017).…”
Section: Nurse Work Environments Collective Efficacy and Missed Nurmentioning
confidence: 99%